Pengaruh kesadaran wajib pajak, pemahaman perpajakan, dan sanksi pajak, terhadap kepatuhan wajib pajak orang pribadi di Kutai Timur - Muhammad Rizal Rafsanjani; Yunita Fitria (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2026)
Taxes are a major source of state revenue and a vital role in financing national development and enhancing public welfare. Tax revenues enable government to fund infrastructure projects, deliver public services, and support strategic national programs, making the achievement of revenue targets essential for sustainable development. One of the most significant components of income tax in Indonesia is Income tax (PPH) 21, which is levied on individual taxpayers’ earnings such as salaries, honoraria, and other forms of remuneration. However, compliance among individual taxpayers remains a persistent challenge. This study aims to examine the effects of taxpayer awareness, tax knowledge, and tax sanctions on individual taxpayer compliance. A quantitative approach, primary data were collected through a Likert scale questionnaire. The sample consisted of 400 individual taxpayers holding a Taxpayer Identification Number (NPWP) in the Kutai Timur region. Data were collected via an online survey using Google forms and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. The result of this study indicate that taxpayer awareness, tax knowledge, and tax sanctions have a positive and significant effect on individual taxpayer compliance. This study contributes to the taxation literature by providing empirical evidence from a regional context.